Peran Agama dalam Bimbingan dan Konseling Islam: Pendekatan, Metode, dan Teknik dalam Meningkatkan Kualitas Konselor dan Klien - Nuril Arifa; Maghvira Fuji Syahrani; Muhamad Reza; Hidayani Syam (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
By highlighting relevant approaches, methods and techniques, this article investigates the role of religion, particularly Islam, in guidance and counselling. Every aspect of guidance and counseling is based on the principle of monotheism contained in the Islamic religion. According to client needs, elective, directive and non-directive methods can be applied. To produce people who are morally and spiritually superior, the Islamic approach combines the values of faith, worship and devotion. Apart from that, this article discusses Islamic counseling methods using tabayyun, al-hikmah, mau'idhah, and mujjadi. The results of the analysis show that Islamic religious-based guidance and counseling is able to overcome clients' psychological, social and spiritual problems effectively and improve relationships between people based on faith in Allah SWT.